Arduino Uno-based water turbidity meter using LDR and LED sensors - P. U. Siahaan, A; Silitonga, Nogar; Iqbal, Muhammad; Aryza, Solly; Fitriani, Wirda; Ramadhan, Zuhri; Tharo, Zuraidah; ., Rusiadi; Hidayat, Rahmad; D. T. P. Nasution, M; Ikhwan, Ali; Azhar, Zulfi; et al. (International Journal of Engineering and Technology, 2018)
Arduino Uno water turbidity gauge has been successfully designed and manufactured. This tool is made using LDR as sensor and led as a light source to measure the water turbidity value and Arduino Uno for data processing. The existence of this tool is already familiar and comfortable to find. However, the price is relatively higher to make this tool is only owned by certain circles only. Nephelometric Method is a method of measuring the turbidity of water by passing a light source on water so that the intensity of light reflected by the substances causing turbidity can be known. With the use of led as a light source and photodiode as a light detector, and combined with processing using Arduino Uno then the voltage obtained from the LDR sensor in the form of analog data is processed into digital data and can be displayed in the LCD.Â Â